Decoding the triad: Knowledge Management, IHRM practices in MNCs & Foreign Subsidiaries – A Systematic Literature Review (2006-2019 - Goswami, Prof. Munmun; Padhi, Dr.Amarnath; Venkatachari, Dr. Kavitha; Aaijaz, Dr. Naila (The journal of contemporary issues in business and government, 2023)
In today’s world, with rapid technological advancement and the blurring lines of nationality, the recent generation entering the workforce employees are less restricted geographically, and more attuned to being a “global villager”. Managing such a workforce requires different HRM practices. As more and more organizations go international, their strategy gets modified, which in turn shapes the HRM policies and practices. Thus, to manage the global workforce, consisting of parent country nationals, host country nationals and many a times third country nationals, IHRM practices requires continuous upgradation. As employees are the epitome knowledge bearers, especially tacit knowledge, understanding the nuances of knowledge management and how it is being affected in MNCs and IHRM practices followed in them, has become key essential for sustainability and continuity of the organization. Hence, through critically reviewing the extant literature (2006–2019), the author addresses the above-mentioned issues and identifies possible areas of future research.